2014
DOI: 10.3389/fnhum.2014.00659
|View full text |Cite
|
Sign up to set email alerts
|

Emotional valence and spatial congruency differentially modulate crossmodal processing: an fMRI study

Abstract: Salient exogenous stimuli modulate attentional processes and lead to attention shifts–even across modalities and at a pre-attentive level. Stimulus properties such as hemispheric laterality and emotional valence influence processing, but their specific interaction in audio-visual attention paradigms remains ambiguous. We conducted an fMRI experiment to investigate the interaction of supramodal spatial congruency, emotional salience, and stimulus presentation side on neural processes of attention modulation. Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…As expected, the bilateral STG responded most strongly to verbal interactions, whereas non-verbal interactions activated visual pathways. The latter finding suggests that during verbal stimulation visual cues are less processed ( Wolf et al, 2014 ). In addition to this clear pattern, the non-verbal, non-auditory interactions yielded a cross-modal modulation in the bilateral STG extending into the MTG.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the bilateral STG responded most strongly to verbal interactions, whereas non-verbal interactions activated visual pathways. The latter finding suggests that during verbal stimulation visual cues are less processed ( Wolf et al, 2014 ). In addition to this clear pattern, the non-verbal, non-auditory interactions yielded a cross-modal modulation in the bilateral STG extending into the MTG.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sweat from social anxiety situations enhanced the processing of fearful facial stimuli only in socially anxious individuals—an impressive example of the integration of fear-relevant cues being influenced by personality traits. The interaction of visual emotion processing with irrelevant auditory cues was also subject of the study by Wolf et al ( 2014 ). The authors demonstrated that visual emotion cues modulated tone processing in the auditory cortex.…”
mentioning
confidence: 99%
“…Previous research has shown that visual processing pathways reach far down into the STG, making it a central hub for the multimodal integration of auditory and visual signals ( Robins et al , 2009 ; Klasen et al , 2011 ). Visual cues can influence responses in auditory cortex ( Harrison and Woodhouse, 2016 ) and facilitate processing in the auditory domain ( Wolf et al , 2014 ). Moreover, the STG supports auditory but not visual sensory imagination ( Zvyagintsev et al , 2013 ).…”
Section: Discussionmentioning
confidence: 99%